UPLC–QTOF/MS‐based metabolomics reveals the mechanism of chronic unpredictable mild stress‐induced hypertension in rats. (30th July 2019) - Wu, Qiong; Xia, De‐Meng; Lan, Fen; Wang, Yang‐Kai; Tan, Xing; Sun, Jia‐Cen; Wang, Wei‐Zhong; Wang, Rui; Peng, Xiao‐Dong; Liu, Min
Abstract: Hypertension is a common chronic disease, and it is the strongest risk factor for cardiovascular disease. Recently, the number of patients with hypertension‐related complications has increased significantly, adding a heavy burden to the public health system. It is known that chronic stress plays an important role in the pathogenesis of cardiovascular diseases such as hypertension and stroke. However, the impact of hypertension on the dysfunctions induced by chronic stress remains poorly understood. In this study, using LC–MS‐based metabolomics, we established a chronic stress model to demonstrate the mechanisms of stress‐induced hypertension. We found that 30 metabolites in chronically stressed rats were changed; of these metabolites, seven had been upregulated, and 23 had been downregulated, including amino acids, phospholipids, carnitines and fatty acids, many of which are involved in amino acid metabolism, cell membrane injury, ATP supply and inflammation. These metabolites are engaged in dysregulated pathways and will provide a targeted approach to study the mechanism of stress‐induced hypertension.